2020
DOI: 10.1055/s-0039-1701027
|View full text |Cite
|
Sign up to set email alerts
|

Novel Use of a Social-Media-Based Survey to Detect Regional Differences in Management of Monochorionic–Diamniotic Twins

Abstract: Objective This study aims to evaluate the utility of social media to distribute a patient survey on differences in management and outcomes of monochorionic–diamniotic (MCDA) pregnancies. Study Design A cross-sectional survey was posted to an English-language MCDA twins patient-centered support group within the social media site, Facebook from April 2, 2018 to June 26, 2018. Subjects were recruited through a technique called “snowballing,” whereby individuals shared the survey to assist with recruitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Previous larger epidemiological studies have found that PN is more prevalent in black than in white patients 17,40 . Our survey population was predominantly female, white and US residents, in line with other studies that also utilized social media platforms to deliver surveys 41–44 . The difference in the demographics seen in our study compared with the previous larger epidemiological studies is likely secondary to socioeconomic differences, as well as access to and engagement with the internet and online social media platforms.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Previous larger epidemiological studies have found that PN is more prevalent in black than in white patients 17,40 . Our survey population was predominantly female, white and US residents, in line with other studies that also utilized social media platforms to deliver surveys 41–44 . The difference in the demographics seen in our study compared with the previous larger epidemiological studies is likely secondary to socioeconomic differences, as well as access to and engagement with the internet and online social media platforms.…”
Section: Discussionsupporting
confidence: 75%
“…The percentage of respondents who completed the survey after starting it (74%) was higher than that of previous studies that similarly utilized Facebook support groups 41,44 . Nonetheless, there is potential for response bias to affect the results.…”
Section: Discussionmentioning
confidence: 64%
“…The lack of diversity among the respondents (eg, overwhelmingly well-educated, high income, married/in a partnership, and private insurance) results from the convenience sampling. While this composition of respondents is not unusual as this tends to be the mix of respondents to online, pregnancy-related surveys ( 16 18 ), we are likely not reaching and surveying those who would be most impacted by disparities in care for both MCDA pregnancies and COVID-19 ( 19 ). Although we are not reaching the most at-risk for disparities in care, it is critical to point out that, although a small percentage, we still see patients who are not receiving standard of care for ultrasounds and for whom COVID-19 is impacting pregnancy management.…”
Section: Discussionmentioning
confidence: 99%
“…This was a nonprobability sampling technique where existing study participants "share" the survey to assist with recruitment. 15,16 Anyone with the survey could freely repost the link to their own profile page or share with members outside of the group. Survey details included instructions to designate a single representative to respond on behalf of each L&D unit.…”
Section: Methodsmentioning
confidence: 99%